205k views
0 votes
Solve the equation 1/t-2=t/8

User Niroshan
by
5.2k points

2 Answers

5 votes

Answer:

Two solutions were found :

t =(16-√288)/-2=8+6√ 2 = 0.485

t =(16+√288)/-2=8-6√ 2 = -16.48

Explanation:

User Indrek Ots
by
5.2k points
2 votes

Answer:

-IF THE EQUATION IS
(1)/(t-2)=(t)/(8), THEN:


t_1=4\\t_2=-2

-IF THE EQUATION IS
(1)/(t)-2=(t)/(8), THEN:


t_1=-16.485\\t_2=0.485

Explanation:

-IF THE EQUATION IS
(1)/(t-2)=(t)/(8) THE PROCEDURE IS:

Multiply both sides of the equation by
t-2 and by 8:


(8)(t-2)((1)/(t-2))=((t)/(8))(8)(t-2)\\\\(8)(1)=(t)(t-2)\\\\8=t^2-2t

Subtract 8 from both sides of the equation:


8-8=t^2-2t-8\\\\0=t^2-2t-8

Factor the equation. Find two numbers whose sum be -2 and whose product be -8. These are -4 and 2:


0=(t-4)(t+2)

Then:


t_1=4\\t_2=-2

-IF THE EQUATION IS
(1)/(t)-2=(t)/(8) THE PROCEDURE IS:

Subtract
(1)/(t) and
2:


(1)/(t)-2=(t)/(8)\\\\(1-2t)/(t)=(t)/(8)

Multiply both sides of the equation by
t:


(t)((1-2t)/(t))=((t)/(8))(t)\\\\1-2t=(t^2)/(8)

Multiply both sides of the equation by 8:


(8)(1-2t)=((t^2)/(8))(8)\\\\8-16t=t^2

Move the
16t and 8 to the other side of the equation and apply the Quadratic formula. Then:


t^2+16t-8=0


t=(-b\±√(b^2-4ac))/(2a)\\\\t=(-16\±√(16^2-4(1)(-8)))/(2(1))\\\\t_1=-16.485\\t_2=0.485

User Stephen K
by
5.9k points